Detection of human papilloma virus in the cervical Pap smears and with polymerase chain reaction technique in the rural area of Western Maharashtra, India - Gurjar, Poorva; Patil, Nanda; Bonde, Vijay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical cancer is the second most common cancer in women worldwide and the most common cancer causing death in developing countries. Recent studies have demonstrated the etiological role of human papilloma virus (HPV) in the development of cervical cancer. The oncogenic strains of HPV produce characteristic cytopathic effect in the cervical epithelial cells which can be recognized in the cervical Pap smears as well as tissue sections. However, definitive identification of virus is dependent on specific techniques like electron microscopy, staining of the capsule antigen with immunocytochemical techniques, identification of viral DNA by in situ hybridization and the most sensitive of all is the PCR technique based on DNA amplification. The objective of this study was to find out the HPV infection in cervical Pap smears and using polymerase chain reaction. To categorize the HPV infection into low risk and high risk group. And to find the association of low and high risk group HPV with squamous intraepithelial lesion and squamous cell carcinoma. And to clinicopathological correlation of high risk HPV. Methods: A two months prospective study was carried from July 2015 to Aug 2015 in our institute to detect HPV infection by Pap smear method as well as using polymerase chain reaction. Results: Total 36 cases were obtained within a prospective study period of 2 months. Per speculum examination did not reveal significant change in any of these cases. Taking PCR as a gold standard, sensitivity, specificity, positive and negative predictive value of Pap smear was determined. Conclusions: Pap smears and HPV DNA testing with PCR play significant role in the early detection of cervical lesions where clinical examination has limitations. High risk HPV detection with the PCR technique can be used as a tool to identify the population at risk for subsequent development of cervical cancer.